2004
DOI: 10.1042/bj20031633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dicarbonyl-induced browning on alpha-crystallin chaperone-like activity: physiological significance and caveats of in vitro aggregation assays

Abstract: Alpha-crystallin is a member of the small heat-shock protein family and functions like a molecular chaperone, and may thus help in maintaining the transparency of the eye lens by protecting the lens proteins from various stress conditions. Non-enzymic glycation of long-lived proteins has been implicated in several age- and diabetes-related complications, including cataract. Dicarbonyl compounds such as methylglyoxal and glyoxal have been identified as the predominant source for the formation of advanced glycat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
83
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 48 publications
8
83
1
1
Order By: Relevance
“…Consistent with this is the independent observation that the heat shock protein HSP27 interacts with the insulin-like growth factor receptor 1 and its signal transducer, the serine/threonine kinase protein Akt, which together modulate adipocyte metabolism (52,53). Diabetes alters the metabolism of the chaperone crystallin ␣, increasing its glycation status (43,44). In the lens of the eye, this biochemical change contributes to cataract formation; its effect in adipose tissue, if any, remains to be determined.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Consistent with this is the independent observation that the heat shock protein HSP27 interacts with the insulin-like growth factor receptor 1 and its signal transducer, the serine/threonine kinase protein Akt, which together modulate adipocyte metabolism (52,53). Diabetes alters the metabolism of the chaperone crystallin ␣, increasing its glycation status (43,44). In the lens of the eye, this biochemical change contributes to cataract formation; its effect in adipose tissue, if any, remains to be determined.…”
Section: Resultssupporting
confidence: 54%
“…The heat shock proteins serve as chaperones, controlling protein folding in the endoplasmic reticulum and their subsequent intracellular trafficking (42). There is a growing body of literature linking chaperone-like molecules to adipogenesis, obesity, and diabetes (43)(44)(45)(46). For example, adipogenesis in 3T3-L1 cells is accompanied by increased expression of the chaperone-related immunophilin, FK-binding protein 51 (47).…”
Section: Resultsmentioning
confidence: 99%
“…Elevated activity of aldose reductase and increased production of sorbitol have been implicated for cataractogenesis in diabetic humans and experimental diabetic animals (89). Studies from our laboratory and by others have reported that in vitro nonenzymatic glycation of a-crystallin resulted in the decreased chaperone activity, which is associated with crosslinking and formation of HMM aggregates (55,56,90,91). Moreover, glycation-induced structural changes in acrystallin are comparable with changes manifested in a-crystallin during diabetic cataract (87).…”
Section: Molecular Chaperone-like Function Of A-crystallin and Eye Lesupporting
confidence: 55%
“…In another study, calf lens ␣A-crystallin was found to be more hydrophobic but showed lower chaperone activity than ␣B-crystallin at room temperature (18). In vitro modification of bovine ␣-crystallin with methylglyoxal enhanced the chaperone-like activity, particularly in aggregation assays, although hydrophobicity showed a decrease (27). Moreover, apparent differences in the temperaturedependent behavior of ␣A-and ␣B-crystallins with respect to chaperone activity, hydrophobicity, and oligomeric size necessitate a critical evaluation of the role of hydrophobicity in ␣A-crystallin and ␣B-crystallin function.…”
Section: Resultsmentioning
confidence: 99%